Hubungan Iklan Mie Sedaap Bersama Choi Siwon dengan Minat Beli di Kalangan Followers - Prushilia Putri Nur Taufik; Mochammad Rochim (Bandung Conference Series: Communication Management, 2022)
Abstract. The development of technology has changed the pattern of life. Especially in terms of developing creations in advertising to get consumers. Products or services can be known by consumers through advertising, this is the initial process in advertising, namely the occurrence of perceptions that touch the human senses. One of the social media, namely Instagram, is now growing rapidly, many people use Instagram social media. Currently, many companies in Indonesia are using social media as a means of promotion because nowadays almost every community has social media and actively uses it, one of which is Instagram. Although Instagram social media is said to be a medium that is able to interact with its consumers, it is necessary to examine the extent to which the goals can be reached when viewed from the advertising function on the @miesedaapid Instagram account. This study aims to determine and understand the relationship between the advertisement of delicious noodles with Choi Siwon and buying interest among Instagram followers @miesedaapid. This study uses the uses and effects theory. The research method used is quantitative with a correlational approach. The population of this study are followers of the Instagram account @miesedaapid. This study used a simple random sampling technique. The sample in this study was 100 respondents based on the results of the slovin formula calculation and the sample was a follower of the @miesedaapid Instagram account and who liked uploads to the @miesedaapid Instagram account in March. Data collection techniques were carried out by distributing questionnaires, literature studies, interviews and analyzed using inferential statistical data analysis techniques with the help of the SPSS application. The results of this study state that there is a relationship between advertising and buying interest among followers of @miesedaapid. The correlation result is 0.884, there is a strong relationship between the delicious noodle advertisement with Choi Siwon with buying interest among followers. Abstrak. Perkembangan teknologi membuat pola kehidupan menjadi berubah. Terutama dalam hal mengembangkan kreasi-kreasi dalam iklan untuk mendapatkan konsumen. Produk barang atau jasa dapat diketahui oleh konsumen melalui iklan, ini merupakan proses awal dalam periklanan yaitu terjadinya persepsi yang menyentuh indra manusia. Salah satu media sosial yaitu Instagram kini sedang berkembang pesat banyak masyarakat menggunakan social media Instagram.Saat ini banyak perusahaan di Indonesia yang memanfaatkan media sosial sebagai sarana promosi karena saat ini hampir setiap masyarakat memiliki media sosial dan aktif menggunkannya salah satunya Instagram. Walaupun media sosial Instagram dikatakan sebagai media yang mampu berinteraksi dengan para konsumennya namun perlu diteliti sejauh mana tujuan yang bisa dijangkau jika dilihat dari fungsi iklan di akun Instagram @miesedaapid. Penelitian ini bertujuan untuk mengetahui dan memahami hubungan antara iklan mie sedaap Bersama Choi Siwon dengan minat beli di kalangan followers Instagram @miesedaapid. Penelitian ini menggunakan teori uses and effect. Metode penelitian yang digunakan adalah kuantitatif dengan pendekatan korelasional. Populasi dari penelitian ini adalah followers dari akun Instagram @miesedaapid. Penelitian ini menggunakan teknik simple random sampling. Sampel pada penelitian ini sebanyak 100 responden yang berdasarkan hasil perhitungan rumus slovin dan sampel merupakan pengikut dari akun Instagram @miesedaapid dan yang menyukai unggahan pada akun Instagram @miesedaapid pada bulan Maret. Teknik pengumpulan data dilakukan dengan menyebarkan kuesioner, studi kepustakaan, wawancara dan dianalisis menggunakan teknik analisis data statistik inferensial dengan bantuan aplikasi SPSS. Hasil penelitian ini menyatakan bahwa terdapat hubungan antara iklan dengan minat beli di kalangan followers @miesedaapid. Didapatkan hasil korelasinya 0,884 terdapat hubungan yang kuat dari iklan mie sedaap bersama Choi Siwon dengan minat beli di kalangan followers.